Implementasi Pengembangan Kurikulum Merdeka pada Mata Pelajaran Al – Qur’an Hadis di Madrasah Ibtidaiyah Misbahul Adhim - Binti Khoirur Rofiah; Sunarto Sunarto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to understand the implementation of the Independent Curriculum in learning the Qur'an and Hadith at MI Misbahul Adhim. With a qualitative approach and field research methods, this research explores the views and experiences of teachers and students regarding their adaptation to curriculum changes. Data were collected through direct observation, in-depth interviews, and review of relevant documents. The research findings reveal that the Independent Curriculum provides more flexibility for educational institutions to design a learning process that is more in line with the needs of students. The main focus of this curriculum is meaningful learning, character building, and the application of integrated technology. However, the implementation of the Independent Curriculum also faces a number of obstacles, such as limited resources, readiness of teaching staff, and changes in mindset in learning. Overall, the Independent Curriculum has significant potential in improving the quality of religious education. This study recommends the need for more intensive support from various parties, including the government, educational institutions, and the community, to ensure the successful implementation of the curriculum. Further research can be focused on identifying factors that influence the success of curriculum implementation and developing more optimal strategies.